THE EFFECT OF MISSOURI MATHEMATICS PROJECT LEARNING MODEL AND SELF REGULATED LEARNING TOWARD STUDENT ACHIEVEMENT - Rindu Hati; Johanes Sapri; Wasidi Wasidi (UNIB Press, 2018)
This research aim to obtain information concerning to the effect of Missouri Mathematics Project (MMP) learning model and self regulated learning toward learning achievement. The research was conducted by using experiment model with design factorial two way analysis in testing hypothesis. In this research, involves 56 from cluster random sampling 86 student’s fifth grade MI Nurul Huda Bengkulu City. Data obtained with the self regulated learning questionnaire instrument self regulated learning and learning achievement data obtained by learning achievement test. The results of two way analysis data shows that students who study with MMP models that have high self regulated learning get better achievement than students who have low self regulated learning, but there is not the influence of MMP models learning and self regulated learning. This reseach recommendations addressed to the teacher in order to take advantage of the learning model is more varied to meet the learning need of studens who have diverse self regulated learning.